Use of Atomized Spray Cutting Fluid Technique for the Turning of a Nickel Base Superalloy. Issue 3 (17th February 2021) - Sivalingam, Vinothkumar; Zhuoliang, Zan; Jie, Sun; Baskaran, S.; Yuvaraj, N.; Gupta, Munish Kumar; Aqib, Mashood Khan
ABSTRACT: The nickel-base superalloys have significant usage in aviation, aerospace and other modern industries owing to its valuable engineering properties, which include good corrosion, creep resistance, high strength and elevated temperature resistance. However, its machinability faces extreme difficulty due to inherent characteristics. In this study, one such attempt has been made to enhance the machinability of the specific nickel-base superalloy i.e. Inconel 718 by using eco-benign cooling approaches, i.e., dry and atomized spray cutting fluid system (vegetable oil with graphite + molybdenum disulfide). A set of turning experiments with ceramic inserts were performed on different combinations of cutting parameters under dry and atomized spray cutting fluid conditions. The important machining indices such as tool wear, surface topography, power consumption, machine vibrations, machining cost, and chip morphology were evaluated subsequently with respect to these two cooling conditions. The overall results reveal that the atomized spray cutting fluid technique can be considered as an alternative cooling technique toward the enhancement of the sustainable machinability compared to dry machining.